The Survey of Oral Health Conditions of Residents Living in a Special Nursing Home for the Elderly - HATORI, Mutsumi; KIMURA, Yuuko; NAGUMO, Masao; SATO, Mayako; MAESATO, Naoko; SAIDA, Akiko; KAKUTA, Saburo; HIYAMA, Kunie (The Journal of Showa University Dental Society, 2000)
Oral health care is significant to improving QOL (quality of life) of handicapped elderlies. Therefore it is necessary to know the oral conditions of these elderlies. This survey was performed by interviews to nurses and by oral examinations of 76 residents living in a special nursing home for the elderly opened at Ohta-ku Tokyo in April 1998. The subjects were 9 males and 67 females. The mean ages were 75.8 for males and 81.7 for females. Most had serious illnesses, including blood circulation disease, cerebrovascular disease, and cranial nerve disease such as Alzheimer's and dementia. The numbers of edenturous persons were 26 and dentate individuals were 50. The oral hygiene of dentate persons was poor, and residual teeth suffered from dental caries or periodontal diseases. The chief oral mucous disease was atrophy of the tongue, and candidiasis was seen in a few persons. There were oral diskinesia and sounds of temporomandibular joints. The average number of residual teeth was 18.5 at the ages of 60 to 64 and decreased with aging. Comparing the relationship between oral diskinesia and the number of residual teeth, the number of teeth showed a tendency to be fewer in subjects with oral diskinesia. These results indicate that elderlies in a special nursing home suffer from various kinds of oral diseases and systemic diseases and need oral health care.